Physical demands of sprinting in professional road cycling - Menaspa, P.; Quod, M.; Martin, D. T.; Peiffer, J. J.; Abbiss, C. R. (International Journal of Sports Medicine, 2015)
The aim of this study was to quantify the demands of road competitions ending with sprints in male professional cycling. 17 races finished with top-5 results from 6 male road professional cyclists (age, 27.0±3.8 years; height, 1.76±0.03 m; weight, 71.7±1.1 kg) were analysed. SRM power meters were used to monitor power output, cadence and speed. Data were averaged over the entire race, different durations prior to the sprint (60, 10, 5 and 1 min) and during the actual sprint. Variations in power during the final 10 min of the race were quantified using exposure variation analysis. This observational study was conducted in the field to maximize the ecological validity of the results. Power, cadence and speed were statistically different between various phases of the race (p<0.001), increasing from 316±43 W, 95±4 rpm and 50.5±3.3 km·h-1 in the last 10 min, to 487±58 W, 102±6 rpm and 55.4±4.7 km·h-1 in the last min prior to the sprint. Peak power during the sprint was 17.4±1.7 W·kg-1. Exposure variation analysis revealed a significantly greater number of short-duration high-intensity efforts in the final 5 min of the race, compared with the penultimate 5 min (p=0.010). These findings quantify the power output requirements associated with high-level sprinting in men`s professional road cycling and highlight the need for both aerobic and anaerobic fitness.